PENANGANAN GELANDANGAN DAN PENGEMIS DI KOTA YOGYAKARTA DITINJAU DARI PERATURAN DAERAH ISTIMEWA YOGYAKARTA NOMOR 1 TAHUN 2014 - Suranto, Suranto; S., Anditia Galih (Res Publica: Jurnal Hukum Kebijakan Publik, 2017)
The Yogyakarta Local Regulation No. 1 Of 2014 is about the handling of homeless and beggars by Social Service Department, Manpower, and Transmigration Department and Public Order Department. The aim of this research is to discover the implementation of Yogyakarta Local Regulation about the handling of homeless and beggars. This journal employs qualitative descriptive approach. The data were collected by field study and case study methods to gain primary and secondary data. The result of the research shows that the implementation of homeless and beggars is done by two steps, controling step and handling step. The controling step is handled by Public Order Department of Yogyakarta. The handling step is handled by Social Service Department, Manpower, and Transmigration Department that consist of represive, coercive, rehabilitation, and social reintegration eforts.